2021
DOI: 10.1002/smll.202100683
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Intermetallic Cu3Sn/Cu Hybrid Electrodes as Efficient Electrocatalysts for Carbon Dioxide Reduction

Abstract: Designing highly selective and cost‐effective electrocatalysts toward electrochemical carbon dioxide (CO2) reduction is crucial for desirable transformation of greenhouse gas into fuels or high‐value chemical products. Here, the authors report intermetallic Cu3Sn that is in situ formed and seamlessly integrated on self‐supported bimodal nanoporous Cu skeleton (Cu3Sn/Cu) via a spontaneous alloying of Sn and Cu as robust electrocatalyst for selective electroreduction of CO2 to CO. By virtue of Sn atoms strengthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Finally, on the basis of machine learning predictions, Al 0.6 Cu 3.4 (100) and AlCu 3 (211) surfaces are specified to be highly selective for hydrocarbons. In addition, the studies of Cu 3 Sn and CuZn in CO 2 RR have been reported, which proves the potential of these bimetallic alloys and further verifies our prediction results.…”
Section: Resultssupporting
confidence: 87%
“…Finally, on the basis of machine learning predictions, Al 0.6 Cu 3.4 (100) and AlCu 3 (211) surfaces are specified to be highly selective for hydrocarbons. In addition, the studies of Cu 3 Sn and CuZn in CO 2 RR have been reported, which proves the potential of these bimetallic alloys and further verifies our prediction results.…”
Section: Resultssupporting
confidence: 87%
“…The definition of ordered intermetallic structure is the solid state compound with the metallic bond, defined stoichiometry, and ordered crystal structure. [84] The performance of intermetallic Sn-based catalysts is also strongly correlated to the composition. Wan process (Figure 4a,b).…”
Section: Atomic Structure Engineeringmentioning
confidence: 99%
“…CO 2 RR FE for (B) V o -CuO­(Sn) and (C) V o -CuO, CuO electrodes. (D) The FE CO and partial current density of V o -CuO­(Sn) compared with other CO 2 -to-CO catalysts. (E) Stability measurement of V o -CuO­(Sn), V o -CuO, CuO­(Sn), and CuO samples at −0.53 V versus RHE in CO 2 -saturated 0.1 M KHCO 3 aqueous solution.…”
Section: Resultsmentioning
confidence: 99%